Plasma-treated poly(ethylene oxide) nanofibers containing tea tree oil/beta-cyclodextrin inclusion complex for antibacterial packaging - Cui, Haiying; Bai, Mei; Lin, Lin (Carbohydrate polymers, 2018)
•The antibacterial PEO nanofibers containing TTO/β-CD-IC was prepared.•The antibacterial activity of PEO nanofibers was enhanced by plasma treatment.•The antibacterial PEO nanofibers had no impact on the sensory quality of beef. This work describes the effect of cold nitrogen plasma to enhance the antibacterial activity of poly(ethylene oxide) (PEO) nanofibers containing antibacterial agent. Beta-cyclodextrin (β-CD) and tea tree oil (TTO) were used as a host-guest to form water-soluble inclusion complex. The encapsulation efficiency of TTO in inclusion complex could reach 73.23% at 60°C. As antibacterial agent, the inclusion complex was encapsulated into PEO matrix by electrospun. After plasma treatment, the release efficiency of antibacterial agent from PEO nanofibers was improved. As a result, the antibacterial activity of PEO nanofibers was enhanced accordingly. The plasma-treated nanofiber membranes achieved the highest antibacterial activity against Escherichia coli O157:H7, which was tested on the beef for 7d, with inhibition efficiently of 99.99% whether at 4°C or 12°C. The plasma-treated PEO nanofiber membranes containing TTO/β-CD inclusion complex (TTO/β-CD-IC) can prolong the shelf-life of beef, suggesting it has potential application in active food packaging.